Motion analysis systems as optimization training tools in combat sports and martial arts - Polak, E.; Kulasa, J.; VencesBrito, A.; Castro, M. A.; Fernandes, O. (Revista de Artes Marciales Asiaticas, 2015)
Introduction: Over the past years, a few review papers about possibilities of using motion analysis systems in sport were published, but there are no articles that discuss this problem in the field of combat sports and martial arts. Aim: This study presents the diversity of contemporary motion analysis systems both, those that are used in scientific research, as well as those that can be applied in daily work of coaches and athletes in combat sports and martial arts. An additional aim is the indication of example applications in scientific research and range of applications in optimizing the training process. It presents a brief description of each type of systems that are currently used in sport, specific examples of systems and the main advantages and disadvantages of using them. The presentation and discussion takes place in the following sections: motion analysis utility for combat sports and martial arts, systems using digital video and systems using markers, sensors or transmitters. Conclusions: Not all types of motion analysis systems used in sport are suitable for combat sports and martial arts. Scientific studies conducted so far showed the usefulness of video-based, optical and electromechanical systems. The use of research results made with complex motion analysis systems, or made with simple systems, local application and immediate visualization is important for the preparation of training and its optimization. It may lead to technical and tactical improvement in athletes as well as the prevention of injuries in combat sports and martial arts.